4CPS-076 Encouraging the responsible use of antibiotics: awareness and understanding among a university student population of a community pharmacy public health campaign in scotland. (March 2019) - Tonna, A; Weidmann, A; Donat, I; Sneddon, J; Cockburn, A; Stewart, D
Abstract : Background: Antimicrobial resistance (AMR) is a significant threat to patient safety globally. European Antibiotic Awareness Day (EAAD) is an annual public health initiative, to raise awareness on how to use antibiotics in a responsible way and NHS Scotland has annually supported EAAD with various resources targeting the public. Purpose: To explore the awareness and understanding of this national campaign among a university student population. Material and methods: A questionnaire was developed comprising: demographics; exposure to media campaign; awareness, knowledge and understanding of campaign; and student recommendations on how the campaign may be enhanced. Question types were a combination of closed, 5-point Likert scales and open response items. Following a review for face and content validity, piloting and ethics approvals, the final version was distributed electronically to all students on all courses registered in a Scottish university. SPSS version 21 facilitated analysis. 15 228 email contacts were sent. Results: One-thousand three-hundred and fifty-eight responses were received (9% response). One-thousand one-hundred and forty-three (84%) were resident in Scotland. Seventy-three per cent were undergraduates, 63% female. Responses were received from all nine university schools, 52 (4.5%), predominantly healthcare students, had heard of EAAD, 31 (2.7%) were familiar with posters advertising the safe use of antibiotics and awareness was mainly through posters in pharmacies. The majority who thought that antibiotics should always be prescribed when having a cold were studying a non-healthcare-related course (5.4%, n=72). Eight-hundred and eighty-one (77%) respondents were unaware that their behaviour in taking antibiotics may influence future effectiveness. Few respondents (7%, n=79) provided an opinion on more effective ways of raising public awareness of this issue, with social media (3%, n=35) being the main choice. Conclusion: A study limitation is that an accurate response rate cannot be determined. Emails were sent to all registered students irespective of whether they lived in Scotland. Any response rate calculated is likely to be lower. A major strength is that good representation from across the university schools was achieved. The research indicates that most respondents had little understanding of the importance of AMR, were not aware of EAAD and had not seen the pharmacy posters. Current approaches need to be revised for more effective dissemination of this issue amongs the general public. Reference and/or acknowledgements: No conflict of interest.